2013
DOI: 10.1051/matecconf/20130607005
|View full text |Cite
|
Sign up to set email alerts
|

Spalling of concrete subjected to blast loading

Abstract: Abstract. This paper presents outcomes of the blast field tests of FRC and reinforced concrete specimens, which were performed in cooperation with the Czech Army corps and Police of the Czech Republic in the military training area Boletice. The numerical evaluation of the experiments focused on the spalling of concrete subjected to blast loading started after the first set of the tests, took almost 3 years and required further small-scale experiments performed in the labs of the Czech Technical University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
3
2
0
Order By: Relevance
“…Based on the analysis of the visible damage, concrete slabs with fibers have better resistance to blast effects, whereas concrete slabs with steel fibers are preferred due to the lower proportion of completely broken slab parts (punctured concrete) caused by the explosion. Better resistance to explosive action in concrete slabs with added fibers compared to elements without added fibers was also observed in other research [28][29][30][31][32][47][48][49][50][51] due to higher tensile and shear strength as well as higher fracture energy and better ductility. Please note that the explosion resistance of the RC slabs in this experimental study is a qualitative term that describes the RC slab resistance to destruction caused by explosives, e.g., how much the sample is damaged and how much properties such as the velocity of the ultrasonic waves through concrete are reduced.…”
Section: Comprehensive Analysis Of the Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Based on the analysis of the visible damage, concrete slabs with fibers have better resistance to blast effects, whereas concrete slabs with steel fibers are preferred due to the lower proportion of completely broken slab parts (punctured concrete) caused by the explosion. Better resistance to explosive action in concrete slabs with added fibers compared to elements without added fibers was also observed in other research [28][29][30][31][32][47][48][49][50][51] due to higher tensile and shear strength as well as higher fracture energy and better ductility. Please note that the explosion resistance of the RC slabs in this experimental study is a qualitative term that describes the RC slab resistance to destruction caused by explosives, e.g., how much the sample is damaged and how much properties such as the velocity of the ultrasonic waves through concrete are reduced.…”
Section: Comprehensive Analysis Of the Resultssupporting
confidence: 78%
“…Comparable test results were observed in previous studies [29][30][31], confirming that an increase in the proportion of polypropylene fibers leads to a reduction in the extent of damage. However, the results of the aforementioned tests showed that the addition of steel fibers did not lead to a reduction in damage [29][30][31].…”
Section: Visual Inspectionsupporting
confidence: 87%
See 3 more Smart Citations